Perceiving gender locally, globally, and intersectionally - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Bingley : Emerald JAI, 2009)
The introduction and 10 essays in this volume address questions about how feminist scholars conceptualize gender and view it in relationship to other attributes of individuals and of social systems. The authors strive for intersectional analyses broadening that approach beyond the gender, race and class paradigm to include sexuality, employing a variety of methodologies, and arguing that intersectionality is, or should be, not just theory, but praxis as well. The topics include the empowerment of women globally; the relationship of gender to international migration; gender differences in organizational participation; heteronormativity in organizations and in the media; the ways that the global affects the local in legislation, the workplace and the academy; the relationship between positive stereotypes of women and support for women's rights; and essentialist themes in men's movements. The discussions of globalization and empowerment and of migration are explicitly transnational in perspective. The remaining essays analyze data gathered in particular locations, but all have broader implications. Three nation-specific essays focus on organizational participation in Brazil, feminism in the Canadian academy, and sexual harassment legislation in Japan. Those on the media, social movements and voluntary organizations, and on modern prejudice are based on data from the United States. All of the authors and co-authors, whether professors emerita or graduate students, are trained in the social sciences. Nevertheless, the essays reflect the increasingly interdisciplinary approach to data and methods that characterizes contemporary feminist writing and research.
Introduction: perceiving gender locally, globally, and intersectionally / Vasilikie Demos, Marcia Texler Segal -- Toward an intersectionality just out of reach: confronting challenges to intersectional practice / Rachel E. Luft, Jane Ward -- Commonsense, gender, and the politics of queer visibility / Celine-Marie Pascale -- "Do you like girls yet?" Heterosexual presumption, homophobia, and pubescence / Jeffery P. Dennis -- Grappling with the relationship between men's endorsement of positive stereotypes of women and support for women's rights / N. Eugene Walls -- Racialized masculinity and discourses of victimization: a comparison of the mythopoetic men's movement and the militia of Montana / Teal Rothschild -- Globalization and gender equality: a critical analysis of women's empowerment in the global economy / Rifat Akhter, Kathryn B. Ward -- Gender in motion: how gender precipitates international migration / Stephanie J. Nawyn, Anna Reosti, Linda Gjokaj -- The private motivations of public action: women's associational lives and political activism in Brazil / Solange Simões, Bruno P.W. Reis, Daniel Biagioni, Fabrício M. Fialho, Natália S. Bueno -- Feminism in the Canadian academy / R.A. Sydie -- How did sexual harassment become a social problem in Japan? The equal employment opportunity law and globalization / Chika Shinohara.
Includes bibliographical references.
Description based on print version record.
Keywords: Gender identity; Sex (Psychology); Gender studies, gender groups; Social Science -- Gender studies; Electronic books